The Influence of Product Quality and Service Quality on Repeat Purchases at the Arsyla Fashion Kids Store - Pirdayanti, Pirdayanti; Ayuniah, Rahmi; Andini, Andini; Hasrat, Nabila Agita; Nurhuda, Nurhuda; Sahabuddin, Dewi Hardiyanti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This research aims to examine the influence of product quality and service quality on repurchase behavior at Arsyla Fashion Kids Palopo. A quantitative research design was applied with a sample size of 30 respondents selected through accidental sampling. Data were collected using three techniques: interviews, observation, and questionnaires. The data were analyzed using multiple linear regression with the assistance of SPSS software. Hypothesis testing was conducted through the F-test and t-test, while the coefficient of determination (R) was employed to assess the explanatory power of the regression model. The findings suggest that both product quality and service quality exert a significant effect on repurchase behavior at Arsyla Fashion Kids Palopo. More specifically, product quality significantly influences repurchase behavior, and service quality likewise demonstrates a significant effect on repeat purchasing decisions.